(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Hymynets V. V. Scientific and methodological aspects of the innovative environment in the region. The article examines the impact of the information society in the formation of information culture teacher. The structure and level of formation of information culture of the teacher due to the necessity of using information technologies in the classroom kompunikatsiynyh to ensure the effectiveness of the learning process.